Metabolic basis of MYC-induced apoptosis - Su, Huizhong (The University of Edinburgh, 2018)
Programmed cell death, known as apoptosis, is widely accepted as a key tumour suppression mechanism. The oncogene MYC promotes cell growth and proliferation but also sensitises cells to apoptosis, which limits its oncogenic potential. MYC-induced apoptosis requires the pro-apoptotic BCL2 family proteins BAX/BAK and can be blocked by anti-apoptotic family members such as BCL2 and BCL-xL. Previous studies have identified glutamine withdrawal as a trigger for MYC-induced apoptosis. Through untargeted metabolomic analyses of cells with perturbed BCL2 family member composition and of cells undergoing glutamine-dependent MYC-induced apoptosis, we found that nucleosides and nucleotides were altered in correlation with apoptotic status. Glutamine is an important biosynthetic substrate and energy source and we show global transcription and translation of the cells decreased upon glutamine withdrawal. However, MYC-activated cells promote transcription and translation even in the absence of glutamine and thus still drive huge demand for energy. Deregulated MYC promotes nucleotide catabolism and depletes cellular energy charge upon glutamine withdrawal, indicating energy shortage driven by MYC. Nucleotide conversion and remodeling by adenylate kinase 2 (AK2) protects cellular energy charge and inhibits MYC-induced apoptosis. These results indicate a homeostatic model for MYC-induced apoptosis based upon mitochondrial energy supply and demand. We propose that the transcriptional activity of MYC drives huge demand for energy to support global transcription and translation and thereby sensitises cells to apoptosis under conditions of limiting energy supply.
Keywords: apoptosis; MYC; BAX/BAK; MYC-activated cells; glutamine; MYC-induced apoptosis